PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA - Selvia Siregar; Nurlina Ariani Harahap; Eva Julyanti (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2025)
This writing aims to understand how the Project-Based Learning (PJBL) model works to influence the mathematical thinking skills of class VIII students at the Darus Sholihin Labuhanbatu Islamic Boarding School. The research relies on a Pretest-Posttest Control Group design and quasi-experimental methodology. Two groups of sample students were: an experimental group that received teaching based on the PJBL model, and a control group that received teaching using traditional techniques. The results show that when compared with the control group, students taught using the PJBL paradigm experienced a significant increase in understanding of mathematical concepts. The PJBL model has a significant effect on students' understanding of mathematical concepts, according to statistical analysis using the T-Test, the significance number is 0.002, less than 0.05. As a result, the project-based learning approach can be considered as a successful substitute for strengthening students' mathematical thinking standards.